2014 13th International Conference on Control Automation Robotics &Amp; Vision (ICARCV) 2014
DOI: 10.1109/icarcv.2014.7064604
|View full text |Cite
|
Sign up to set email alerts
|

Uncalibrated stereo visual servoing for manipulators using virtual impedance control

Abstract: In this paper, we present an uncalibrated positionbased fixed-camera Visual Servoing for robot manipulators, where the goal is to track the 3D position and orientation of the target. The stereo system with 2 USB cameras is uncalibrated with respect to the robot base frame and the transformation between them is estimated on-line while performing the task. Dynamic impedance control is designed to generate a dynamic trajectory for the robot manipulator considering the dynamic environment constraints, such as: rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In this paper, the design of the robot system for the LESS scenario adopts an autonomous control idea that makes use of the visual servo method to position. In the uncalibrated stereo visual servo control, there exist some factors to be considered, such as the visual scope of the camera and collision with other objects within the robotic workspace . In order to obtain the expected control effect, impact analysis of k p and dt for the robotic motion were carried out.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the design of the robot system for the LESS scenario adopts an autonomous control idea that makes use of the visual servo method to position. In the uncalibrated stereo visual servo control, there exist some factors to be considered, such as the visual scope of the camera and collision with other objects within the robotic workspace . In order to obtain the expected control effect, impact analysis of k p and dt for the robotic motion were carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Various parameters of a robotic vision system are likely to change in the complex and harsh space environment, which will have a serious impact on the accuracy of the visual servo. Moreover, frequent system recalibration will greatly increase the cost and workload, and its feasibility is quite low [19][20][21][22]. For these reasons, research into uncalibrated visual servos is very significant.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is required by some safety standards, such as ISO 10218 and ISO 15066, and widely used in industries and literatures (Kulić and Croft, 2007; Kulic´, 2006; Zanchettin et al , 2016). The safety of the robot’s operations is usually enhanced further by implementing some obstacle avoidance strategies such as repelling potential fields (Khatib, 1986; Kim and Khosla, 1992; Park et al , 2008; Zavlangas and Tzafestas, 2000), virtual impedances (Cai et al , 2014; Lacevic et al , 2013; Lo et al , 2016; Arai et al , 1989; Khansari-Zadeh and Khatib, 2017), elastic strips (Brock and Khatib, 2002; Sun et al , 2016) and human-like steering (Fajen and Warren, 2003; Huang et al , 2006; Fajen et al , 2003; Ijspeert et al , 2013; Hoffmann et al , 2009; Pastor et al , 2013) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose a combination of the DMP framework with the virtual impedance method to avoid obstacles in real-time. The virtual impedance method for real-time obstacle avoidance was first proposed by Arai et al (Arai et al , 1989) and has found extensive applications (Cai et al , 2014; Lacevic et al , 2013; Lo et al , 2016; Zavlangas and Tzafestas, 2000; Khansari-Zadeh and Khatib, 2017). Combination of the virtual impedance method with the DMP framework eliminates the need for manipulating the original DMP formulation.…”
Section: Introductionmentioning
confidence: 99%